Teoria do efeito estético articulada à teoria histórico-cultural e BNCC: contribuições para o ensino de leituras literárias - Silva, Carolaine Marinho da (2023)
The National Common Curricular Base (BNCC) prioritizes the formation of readers-enjoyers. To fulfil such task, the mediating teachers need theoretical and methodological principles. In order to assist the teaching performance, its crucial the consideration of the Aesthetic Effect Theory (AET) articulated with the Historical-Cultural Theory (THC) accordingly with Santos (2007; 2009) for the development of the literary competences proposed in the BNNC – in the sphere of Elementary Education (Final Years) and High School. Based on this, the following question’s risen: can the AET articulated with Santo’s (2007; 2009) THC contribute to the development of competences contained in the artistic-literary field of the BNCC? Our hypothesis is that such articulation offers support for addressing literature in the classroom in line with the BNCC’s propositions, as it can underpin the Mapping of Readers' Aesthetic Experience (MAPEE) and the application of the Metaprocedimental Didactic Script (RDM). These tools can favour the achievement of competences outlined in the document. The general objective of this work’s verifying the viability articulating the Aesthetic Effect Theory (AET) with the Historical-Cultural Theory (THC) in the teaching of literary readings as advocated by the BNCC. Towards its achieving, the specific objectives are: to examine the premisses of the BNCC, especially those regarding the teaching of literature; to theoretically discuss the AET articulated with Santos’s (2007; 2009) THC and its possible contributions to the teaching of literary readings in the school setting; to present a proposal for teaching literary reading to the 9th year of Elementary School based on the AET articulated with the THC and the guidelines outlined in the BNCC. The methodological approach's qualitative, utilizing exploratory and bibliographical research. The main theoretical contributions are Santos (2007; 2009; 2014), Iser (1996), Bezerra (2021) and Santos and Costa (2020). The results indicate that, in addition to those theoretical contributions, this articulation also assists methodologically the teacher's performance.